Discourse in Linda's Voice Recording on the News of the Tragedy of Vina Cirebon's Murder and Death - Sandi S Nani; Sayama Malabar; Ellyana Hinta (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
This study aims to describe the forms of discourse in Linda’s voice recordings related to the news of the Vina Cirebon murder and death tragedy, the factors influencing the use of discourse, the forms of forensic language employed, and their relevance to Indonesian language learning. The research was conducted in 2025 using Linda’s voice recordings obtained from YouTube as the research object. The population consisted of all utterances contained in the recordings, while the sample included utterances containing elements of forensic discourse. The researcher served as the primary research instrument, supported by data transcripts. Data were analyzed using forensic discourse analysis based on Coulthard and Johnson’s framework, focusing on word choice, utterance structure, linguistic patterns, and the speaker’s social and emotional context. The findings reveal that the discourse in Linda’s voice recordings consists of narrative discourse, denial, self-defense, and emotional expressions. The use of discourse is influenced by emotional conditions, speech situations, personal experiences, and the speaker’s social context. The identified forms of forensic language include word repetition, vowel prolongation, pauses, paralinguistic elements, and disfluencies that reflect the speaker’s emotional state. Furthermore, the findings demonstrate their relevance to Indonesian language learning, particularly in listening, reading and viewing, and speaking activities through the use of audiovisual texts as contextual and authentic learning materials.